Comprehensive elaboration of circular RNA in multiple myeloma - Zhu, Chunsheng; Guo, Aoxiang; Sun, Bao; Zhou, Zheng (Frontiers in Pharmacology, 2022)
Circular RNAs (circRNAs), a novel category of endogenous non-coding RNAs, are usually well conserved across different species with a covalent closed-loop structure. Existing and emerging evidence confirms that circRNAs can function as regulators of alternative splicing, microRNA and RNA-binding protein sponges and translation, as well as gene transcription. In consideration of their multi-faceted functions, circRNAs are critically involved in hematological malignancies including multiple myeloma (MM). In particular, circRNAs have been found to play vital roles in tumor microenvironment and drug resistance, which may grant them potential roles as biomarkers for MM diagnosis and targeted therapy. In this review, we comprehensively elaborate the current state-of-the-art knowledge of circRNAs in MM, and then focus on their potential as biomarkers in diagnosis and therapy of MM.